Ascariasis with Paralytic Ileus and Acute Gastroenteritis in a 2-Year-Old Child: A Case Report - Andi Husni Esa Darussalam; Irmayanti Irmayanti; Nurfachanti Fattah (Journal La Medihealtico, 2026)
Ascariasis, caused by Ascaris lumbricoides, is a common soil-transmitted helminth infection among children in developing countries. Severe infestation may cause gastrointestinal complications, including intestinal obstruction and ileus. This case report describes the clinical presentation, diagnostic findings, and management of a pediatric patient with ascariasis complicated by ileus, acute gastroenteritis, dehydration, and electrolyte imbalance.A 2-year-old girl presented with watery diarrhea for three days, vomiting, fever, decreased appetite, and a history of passing worms in her stool. Physical examination revealed a moderately ill appearance, a tympanic abdomen, and decreased bowel peristalsis. Laboratory findings showed eosinophilia, basophilia, hypokalemia at 3.2 mmol/L, and hypochloremia at 93.1 mmol/L. Stool examination revealed watery stool with mucus, 6–11 leukocytes per high-power field, and Ascaris lumbricoides eggs. Abdominal radiography demonstrated dilated small and large bowel loops with a herringbone pattern suggestive of ileus.The patient was diagnosed with ascariasis complicated by ileus, acute gastroenteritis, mild-to-moderate dehydration, and electrolyte imbalance. Management included intravenous rehydration, nasogastric decompression, ondansetron, albendazole 400 mg as a single dose, zinc supplementation, oral rehydration therapy, and empirical ceftriaxone. During hospitalization, gastrointestinal symptoms gradually improved, accompanied by continued passage of worms in the stool.This case emphasizes the importance of prompt diagnosis and comprehensive management of complicated pediatric ascariasis. Hygiene education, environmental sanitation, and regular deworming remain essential to prevent infection and reinfection in endemic areas.